Catheterobronchial fistula due to vena cava superior thrombosis as a late complication of ventriculoatrial shunt - Parízek, J; Nytra, T; Zemánková, M; Eliás, P; Sercl, M; Nĕmecková, J; Jakubec, J (Child's nervous system, 1994)
A case of a catheterobronchial fistula as a rare late complication of a ventriculoatrial shunt is reported. The ventriculoatrial shunt was implanted in a 4-month-old boy suffering from extreme postinfectious hydrocephalus. During the following years, twelfth nerve palsy on the right, vertebralgias, and salty taste sensations in the mouth associated with intermittent coughing and swelling of the neck and supraclavicular region on the right side developed. Valvography established a diagnosis of fistula 12 years after the implantation of a shunt. Ultrasonography of the neck and mediastinum and contrast-enhanced dynamic computed tomographic scanning demonstrated a catheterobronchial fistula to the subsegmental bronchus of the anterior segment of the right upper lung lobe, a thrombosis of the right internal jugular and both right and left brachiocephalic veins and the superior vena cava, and an extensive collateral venous system mainly draining into the azygos vein. Normalization of cerebrospinal fluid and blood flow and pressure allowed extraction of the "atrial" catheter without complications. One year after surgery the boys is in good health and without signs of shunt dependence.
Keywords: hydrocefalus; vena cava superior; Infant; ventrikuloperitoneální zkrat; bronchografie; Tomography, X-Ray Computed; Trachea; lidé; trombóza; Vena Cava, Superior; trachea; mozek; Hydrocephalus; píštěle; Male; Ventriculoperitoneal Shunt; kojenec; Brain; Thrombosis; počítačová rentgenová tomografie; mužské pohlaví; Fistula; Bronchography; Humans